PENGGUNAAN E-LEARNING SEBAGAI MEDIA LITERASI DIGITAL DALAM MENINGKATKAN GERAKAN MERDEKA BELAJAR - Eny Wahyu Suryanti; Any Ikawati (Prosiding Seminar Nasional Indonesia, 2025)
The research aims to describe the use of e-learning as a digital literacy media in increasing the independent learning movement. Digital literacy in the independent curriculum aims to increase students' interest in reading and writing. E-learning was chosen as a digital literacy media to facilitate access to learning activities. This research uses a descriptive qualitative approach and case study research type. The research location is Madrasah Ibtidaiyah Negeri 1 Malang City. Sources of research data were obtained from the head of the madrasah, deputy head of curriculum, teachers, and students. The research data collection techniques through the stages of interviews, documentation, and observation. Research data analysis includes; data collection techniques, data reduction, data presentation, and conclusion drawing. The results of the study can be concluded that the use of e-learning as a digital literacy media in increasing the independent learning movement in Madrasah Ibtidaiyah Negeri 1 Malang City can be carried out well with the support of internet access speed and adequate digital-based infrastructure. The use of madrasah e- learning includes several forms of online-based activities; 1) teaching and learning activity media, 2) madrasah discussion activity forums, 3) madrasah video conferences, 4) student learning evaluation media, 5) monitoring media for the implementation of learning activities, and 6) information media for student learning outcomes. E-learning facilitates the implementation of learning activities in the independent curriculum.